2013
DOI: 10.1093/annonc/mdt168
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of fish and meats and risk of hepatocellular carcinoma: the European Prospective Investigation into Cancer and Nutrition (EPIC)

Abstract: In this large European cohort, total fish intake is associated with lower HCC risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
70
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(78 citation statements)
references
References 29 publications
7
70
0
1
Order By: Relevance
“…We postulate that these differences in intake levels and food sources of fat could account for the non‐significant associations with saturated and monounsaturated fats in our study. Finally, our finding of an association between higher omega‐6 to omega‐3 PUFA ratio and increased risk of HCC in our nested case–control study, especially for the non‐viral hepatitis related HCC, was indirectly consistent with reports from the Japanese cohort and the EPIC cohort that fish or omega‐3 PUFA intake could reduce HCC risk .…”
Section: Discussionsupporting
confidence: 90%
“…We postulate that these differences in intake levels and food sources of fat could account for the non‐significant associations with saturated and monounsaturated fats in our study. Finally, our finding of an association between higher omega‐6 to omega‐3 PUFA ratio and increased risk of HCC in our nested case–control study, especially for the non‐viral hepatitis related HCC, was indirectly consistent with reports from the Japanese cohort and the EPIC cohort that fish or omega‐3 PUFA intake could reduce HCC risk .…”
Section: Discussionsupporting
confidence: 90%
“…An inverse association observed between liver cancer and white meat (fish or poultry) intake (20) was confirmed in our study. An inverse correlation between the liver cancer mortality and vegetable and fruit consumption was observed in Serbia as well as in many reports (18,19). This probable effect has been related to specific micronutrients contained in vegetables and fruit.…”
Section: Discussionmentioning
confidence: 55%
“…Coffee has also been shown as a protective factor in individuals infected with HBV or HCV (17). In several studies, inverse associations were observed for vegetable and fruit intake, and fish and eggs consumption, while meat intake was directly associated with risk of liver cancer (18)(19)(20). Some other studies did not confirm these findings (21)(22)(23)).…”
Section: Introductionmentioning
confidence: 99%
“…An inverse association between total fat intake and risk of HCC (per 10 g/day HR 0.80; 95% CI 0.65-0.99) has been observed and appears to be mainly driven by monounsaturated fats [30] . Total fish intake was also inversely associated with HCC risk (per 20 g/day HR 0.83; 95% CI 0.74-0.95) while there was no association with meat consumption [31] . Higher consumption of dietary fiber (per 10 g/day HR 0.70; 95% CI 0.52-0.93), but not the intake of total carbohydrate, or the glycemic load or the glycemic index of diet, influenced the risk for HCC significantly [32] .…”
Section: Composition Of the Dietmentioning
confidence: 93%